Operationalising resilience-based management at scale: A meta-adaptive blueprint from the Great Barrier Reef crown-of-thorns starfish control program - Samuel A. Matthews; Michael Bode; Roger Beeden; Mary C. Bonin; Cameron S. Fletcher; Brigid Kerrigan; Isobel Ryan; Jennifer Wilmes; Alice White; David H. Williamson (Biological Conservation, 2026)

Effects of Nutrition Interventions on Inflammatory Biomarkers and Quality of Life in Adults with Multiple Sclerosis: A Scoping Review - C. Bode; C. Sealey Potts; A. Hashmi (Journal of the Academy of Nutrition and Dietetics, 2025)

Enhancing Nutrition Intervention Monitoring Through Computed Tomography Body Composition Assessment: A Case Study in Esophageal and Gastric Adenocarcinoma - M. Garcia Luis; C. Bury; A. Bode (Journal of the Academy of Nutrition and Dietetics, 2025)

Correction: Thrombin receptor PAR4 cross-activates the tyrosine kinase c-met in atrial cardiomyocytes - Claudia Mittendorff; Issam Abu-Taha; Lena Kassler; Tobias Hustedt; Stephanie Wolf; Johannes G. Bode; Markus Kamler; Dobromir Dobrev; Anke C. Fender (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Correction: Thrombin receptor PAR4 cross-activates the tyrosine kinase c-met in atrial cardiomyocytes - Claudia Mittendorff; Issam Abu-Taha; Lena Kassler; Tobias Hustedt; Stephanie Wolf; Johannes G. Bode; Markus Kamler; Dobromir Dobrev; Anke C. Fender (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Thrombin receptor PAR4 cross-activates the tyrosine kinase c-met in atrial cardiomyocytes - Claudia Mittendorff; Issam Abu-Taha; Lena Kassler; Tobias Hustedt; Stephanie Wolf; Johannes G. Bode; Markus Kamler; Dobromir Dobrev; Anke C. Fender (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)
Thrombin supports coagulation-independent inflammation via protease-activated receptors (PAR). PAR4 is specifically increased in obese human atria, correlating with NLRP3 inflammasome activation. PAR4-mediated NLRP3 inflammasome activation in atrial cardiomyocytes is not known, nor have signaling partners been identified. Thrombin transactivates the hepatocyte growth factor receptor in some cancer cells, so we examined PAR4/c-met cross-talk in atrial cardiomyocytes and its possible significance in obesity. Cardiomyocytes from right atrial appendages (RAA) of obese patients expressed more PAR1 and PAR4 compared to non-obese. In HL-1 atrial cardiomyocytes, thrombin induced caspase-1 auto-activation and IL-1β maturation; IL-1β secretion was evoked by PAR4-activating peptide (AP), but not PAR1-AP. PAR4-AP additionally increased phosphorylated CaMKII-Thr287, mTOR-Ser2481, and Akt-Ser473 while suppressing AMPK-Thr172 phosphorylation. Total kinase levels were largely unaltered. PAR4AP rapidly increased phosphorylated c-met in HL-1 cells and over time also transcriptionally upregulated c-met. The c-met inhibitor SGX-523 abrogated the effects of PAR4-AP on CaMKII/AKT/mTOR phosphorylation but did not affect PAR4-stimulated IL-1β production. Obese human RAA contained more IL-1β, phospho-c-met, and phospho-mTOR than non-obese RAA; CamKII phosphorylation was not modified. Atria from high-fat diet (HFD) versus chow-fed mice also contained more IL-1β, together with higher myeloperoxidase activity, Acta2 mRNA total and phosphorylated c-met; these increases were blunted in PAR4 -/- HFD-fed mice. Thrombin cross-activates c-met via PAR4 in atrial cardiomyocytes. Transactivated c-met contributes partially to PAR4-mediated signaling, but NLRP3 inflammasome activation appears to be largely independent of c-met. Abundance of PAR4 and activated c-met increases with obesity, providing therapeutic targets for management of adiposity-driven AF.

The thrombin receptor PAR4 supports visceral adipose tissue inflammation - Sonja Kleeschulte; Vivien Fischinger; Lisa Öhlke; Johannes Bode; Markus Kamler; Dobromir Dobrev; Maria Grandoch; Anke C. Fender (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
Thrombin inhibition suppresses adiposity, WAT inflammation and metabolic dysfunction in mice. Protease-activated receptor (PAR)1 does not account for thrombin-driven obesity, so we explored the culprit role of PAR4 in this context. Male WT and PAR-4 -/- mice received a high fat diet (HFD) for 8 weeks, WT controls received standard chow. Body fat was quantified by NMR. Epididymal WAT was assessed by histology, immunohistochemistry, qPCR and lipase activity assay. 3T3-L1 preadipocytes were differentiated ± thrombin, acutely stimulated ± PAR4 activating peptide (AP) and assessed by immunoblot, qPCR and U937 monocyte adhesion. Epicardial adipose tissue (EAT) from obese and lean patients was assessed by immunoblot. PAR4 was upregulated in mouse WAT under HFD. PAR4 -/- mice developed less visceral adiposity and glucose intolerance under HFD, featuring smaller adipocytes, fewer macrophages and lower expression of adipogenic (leptin, PPARγ) and pro-inflammatory genes (CCL2, IL-1β) in WAT. HFD-modified activity and expression of lipases or perilipin were unaffected by PAR4 deletion. 3T3-L1 adipocytes differentiated with thrombin retained Ki67 expression, further upregulated IL-1β and CCL2 and were more adhesive for monocytes. In mature adipocytes, PAR4-AP increased phosphorylated ERK1/2 and AKT, upregulated Ki67, CCl2, IL-β and hyaluronan synthase 1 but not TNF-α mRNA, and augmented hyaluronidase-sensitive monocyte adhesion. Obese human EAT expressed more PAR4, CD68 and CD54 than lean EAT. PAR4 upregulated in obesity supports adipocyte hypertrophy, WAT expansion and thrombo-inflammation. The emerging PAR4 antagonists provide a therapeutic perspective in this context beyond their canonical antiplatelet action.

Spatial and temporal patterns of nutrients and their environmental impacts from the agriculture sector in India - Lilian Bode; Arthur H. W. Beusen; Stefan C. Dekker; Alexander F. Bouwman (Regional Environmental Change, 2023)
Since the launch of the Green Revolution (GR) in Indian agriculture in the 1960s, Indian food production has successfully become self-sufficient but this has also led to increasing soil nitrogen (N) surpluses and various negative environmental impacts, such as NH 3 emissions. Using the IMAGE Global Nutrient Model, this study explores the development of food production, soil N surpluses and associated NH 3 emissions in India during the GR; the use of subnational data for compiling spatially explicit maps of N inputs (N fertilizers, manure N, biological N fixation, atmospheric deposition) and outputs (crop harvest, grazing) was compared with results using country-scale data. The results show that in the period 1960–2010 food production growth was dramatic (374%), particularly in the region of the GR states (Punjab, Haryana and western Uttar Pradesh). This production increase was primarily based on spectacular increases in crop yields and N inputs. However, due to slowly changing nutrient use efficiency, N surpluses and associated NH 3 emissions increased rapidly, with hotspots especially in the GR states. Maps using data at subnational scale yield a better representation of spatial heterogeneities of the soil N surpluses, emissions and environmental impacts than maps based on country data. This is beneficial for effect calculations, as the location of negative environmental side effects strongly depends on the location of soil N and P surpluses.

Pacemaker-lead-associated thrombosis in dogs: a multicenter retrospective study - C. McGrath; A. Dixon; C. Hirst; E.F. Bode; T. DeFrancesco; R. Fries; S. Gordon; D. Hogan; Y. Martinez Pereira; E. Mederska; S. Ostenkamp; K.T. Sykes; et al. (Journal of Veterinary Cardiology, 2023)

Differences in Left Ventricular Enlargement Secondary to Chronic Volume Loading Between English Springer Spaniels and Two Similar Sporting Breeds - D. Dickson; E. Bode; C. Linney; E. Dutton; D. Caivano; T. Bispo; J. Harris; M. Rishniw (Journal of Veterinary Cardiology, 2023)

Comparative pathology of VIC01 isolate and Omicron variant of SARS-CoV-2 infection, including a rechallenge model, in the Golden Syrian hamster - E. Rayner; K. Ryan; Y. Hall; L. Hunter; C. Kennard; J. Edun Hughes; J. Salguero Bodes (Journal of Comparative Pathology, 2023)

Pro- and anti-inflammatory macrophages express a sub-type specific purinergic receptor profile - J. Merz; A. Nettesheim; S. von Garlen; P. Albrecht; B. S. Saller; J. Engelmann; L. Hertle; I. Schäfer; D. Dimanski; S. König; L. Karnbrock; K. Bulatova; et al. (Purinergic Signalling, 2021)
Extracellular nucleotides act as danger signals that orchestrate inflammation by purinergic receptor activation. The expression pattern of different purinergic receptors may correlate with a pro- or anti-inflammatory phenotype. Macrophages function as pro-inflammatory M1 macrophages (M1) or anti-inflammatory M2 macrophages (M2). The present study found that murine bone marrow-derived macrophages express a unique purinergic receptor profile during in vitro polarization. As assessed by real-time polymerase chain reaction (PCR), Gαs-coupled P1 receptors A2A and A2B are upregulated in M1 and M2 compared to M0, but A2A 15 times higher in M1. The ionotropic P2 receptor P2X 5 is selectively upregulated in M1- and M2-polarized macrophages. P2X 7 is temporarily expressed in M1 macrophages. Metabotropic P2Y receptors showed a distinct expression profile in M1 and M2-polarized macrophages: Gαq coupled P2Y 1 and P2Y 6 are exclusively upregulated in M2, whereas Gαi P2Y 13 and P2Y 14 are overexpressed in M1. This consequently leads to functional differences between M1 and M2 in response to adenosine di-phosphate stimulation (ADP): In contrast to M1, M2 showed increased cytoplasmatic calcium after ADP stimulation. In the present study we show that bone marrow-derived macrophages express a unique repertoire of purinergic receptors. We show for the first time that the repertoire of purinergic receptors is highly flexible and quickly adapts upon pro- and anti-inflammatory macrophage differentiation with functional consequences to nucleotide stimulation.

Effect of alccofine and fly ash on analytical methods of self-compacting concrete - Bode Venkata Kavyateja; J. Guru Jawahar; C. Sashidhar (Innovative Infrastructure Solutions, 2020)

Quantitative trait loci and differential gene expression analyses reveal the genetic basis for negatively associated β-carotene and starch content in hexaploid sweetpotato [Ipomoea batatas (L.) Lam.] - Dorcus C. Gemenet; Guilherme da Silva Pereira; Bert De Boeck; Joshua C. Wood; Marcelo Mollinari; Bode A. Olukolu; Federico Diaz; Veronica Mosquera; Reuben T. Ssali; Maria David; Mercy N. Kitavi; Gabriela Burgos; et al. (Theoretical and Applied Genetics, 2020)
Key message β-Carotene content in sweetpotato is associated with the Orange and phytoene synthase genes; due to physical linkage of phytoene synthase with sucrose synthase , β-carotene and starch content are negatively correlated. Abstract In populations depending on sweetpotato for food security, starch is an important source of calories, while β-carotene is an important source of provitamin A. The negative association between the two traits contributes to the low nutritional quality of sweetpotato consumed, especially in sub-Saharan Africa. Using a biparental mapping population of 315 F 1 progeny generated from a cross between an orange-fleshed and a non-orange-fleshed sweetpotato variety, we identified two major quantitative trait loci (QTL) on linkage group (LG) three (LG3) and twelve (LG12) affecting starch, β-carotene, and their correlated traits, dry matter and flesh color. Analysis of parental haplotypes indicated that these two regions acted pleiotropically to reduce starch content and increase β-carotene in genotypes carrying the orange-fleshed parental haplotype at the LG3 locus. Phytoene synthase and sucrose synthase, the rate-limiting and linked genes located within the QTL on LG3 involved in the carotenoid and starch biosynthesis, respectively, were differentially expressed in Beauregard versus Tanzania storage roots. The Orange gene, the molecular switch for chromoplast biogenesis, located within the QTL on LG12 while not differentially expressed was expressed in developing roots of the parental genotypes. We conclude that these two QTL regions act together in a cis and trans manner to inhibit starch biosynthesis in amyloplasts and enhance chromoplast biogenesis, carotenoid biosynthesis, and accumulation in orange-fleshed sweetpotato. Understanding the genetic basis of this negative association between starch and β-carotene will inform future sweetpotato breeding strategies targeting sweetpotato for food and nutritional security.

Correction to: Ocean zoning within a sparing versus sharing framework - Jennifer McGowan; Michael Bode; Matthew H. Holden; Katrina Davis; Nils C. Krueck; Maria Beger; Katherine L. Yates; Hugh P. Possingham (Theoretical Ecology, 2018)

Ocean zoning within a sparing versus sharing framework - Jennifer McGowan; Michael Bode; Matthew H. Holden; Katrina Davis; Nils C. Krueck; Maria Beger; Katherine L. Yates; Hugh P. Possingham (Theoretical Ecology, 2018)

Reef-fish larval dispersal patterns validate no-take marine reserve network connectivity that links human communities - Rene A. Abesamis; Pablo Saenz-Agudelo; Michael L. Berumen; Michael Bode; Claro Renato L. Jadloc; Leilani A. Solera; Cesar L. Villanoy; Lawrence Patrick C. Bernardo; Angel C. Alcala; Garry R. Russ (Coral Reefs, 2017)

Large‐scale, multidirectional larval connectivity among coral reef fish populations in the Great Barrier Reef Marine Park - David H. Williamson; Hugo B. Harrison; Glenn R. Almany; Michael L. Berumen; Michael Bode; Mary C. Bonin; Severine Choukroun; Peter J. Doherty; Ashley J. Frisch; Pablo Saenz‐Agudelo; Geoffrey P. Jones (Molecular Ecology, 2016)
Larval dispersal is the key process by which populations of most marine fishes and invertebrates are connected and replenished. Advances in larval tagging and genetics have enhanced our capacity to track larval dispersal, assess scales of population connectivity, and quantify larval exchange among no‐take marine reserves and fished areas. Recent studies have found that reserves can be a significant source of recruits for populations up to 40 km away, but the scale and direction of larval connectivity across larger seascapes remain unknown. Here, we apply genetic parentage analysis to investigate larval dispersal patterns for two exploited coral reef groupers ( Plectropomus maculatus and Plectropomus leopardus ) within and among three clusters of reefs separated by 60–220 km within the Great Barrier Reef Marine Park, Australia. A total of 69 juvenile P. maculatus and 17 juvenile P. leopardus (representing 6% and 9% of the total juveniles sampled, respectively) were genetically assigned to parent individuals on reefs within the study area. We identified both short‐distance larval dispersal within regions (200 m to 50 km) and long‐distance, multidirectional dispersal of up to ~250 km among regions. Dispersal strength declined significantly with distance, with best‐fit dispersal kernels estimating median dispersal distances of ~110 km for P. maculatus and ~190 km for P. leopardus . Larval exchange among reefs demonstrates that established reserves form a highly connected network and contribute larvae for the replenishment of fished reefs at multiple spatial scales. Our findings highlight the potential for long‐distance dispersal in an important group of reef fishes, and provide further evidence that effectively protected reserves can yield recruitment and sustainability benefits for exploited fish populations.

Minimizing the Cost of Keeping Options Open for Conservation in a Changing Climate - MORENA MILLS; SAM NICOL; JESSIE A. WELLS; JOSÉ J. LAHOZ‐MONFORT; BRENDAN WINTLE; MICHAEL BODE; MARTIN WARDROP; TERRY WALSHE; WILLIAM J. M. PROBERT; MICHAEL C. RUNGE; HUGH P. POSSINGHAM; EVE MCDONALD MADDEN (Conservation Biology, 2014)
Policy documents advocate that managers should keep their options open while planning to protect coastal ecosystems from climate‐change impacts. However, the actual costs and benefits of maintaining flexibility remain largely unexplored, and alternative approaches for decision making under uncertainty may lead to better joint outcomes for conservation and other societal goals. For example, keeping options open for coastal ecosystems incurs opportunity costs for developers. We devised a decision framework that integrates these costs and benefits with probabilistic forecasts for the extent of sea‐level rise to find a balance between coastal ecosystem protection and moderate coastal development. Here, we suggest that instead of keeping their options open managers should incorporate uncertain sea‐level rise predictions into a decision‐making framework that evaluates the benefits and costs of conservation and development. In our example, based on plausible scenarios for sea‐level rise and assuming a risk‐neutral decision maker, we found that substantial development could be accommodated with negligible loss of environmental assets. Characterization of the Pareto efficiency of conservation and development outcomes provides valuable insight into the intensity of trade‐offs between development and conservation. However, additional work is required to improve understanding of the consequences of alternative spatial plans and the value judgments and risk preferences of decision makers and stakeholders. Minimizando el Costo de Mantener Opciones Abiertas para la Conservación en un Clima Cambiante

A physical map of the Chinese chestnut (Castanea mollissima) genome and its integration with the genetic map - Guang-Chen Fang; Barbara P. Blackmon; Margaret E. Staton; C. Dana Nelson; Thomas L. Kubisiak; Bode A. Olukolu; David Henry; Tatyana Zhebentyayeva; Christopher A. Saski; Chun-Huai Cheng; Megan Monsanto; Stephen Ficklin; et al. (Tree Genetics & Genomes, 2013)

Heterogeneity of the humoral immune response following Staphylococcus aureus bacteremia - N. J. Verkaik; H. A. Boelens; C. P. de Vogel; M. Tavakol; L. G. M. Bode; H. A. Verbrugh; A. van Belkum; W. J. B. van Wamel (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Hypothermic storage of isolated human hepatocytes: a comparison between University of Wisconsin solution and a hypothermosol platform - Alina Ostrowska; Kenan Gu; Donald C. Bode; Robert G. Van Buskirk (Archives of Toxicology, 2009)

Continuous and filter-based measurements of PM2.5 nitrate and sulfate at the Fresno Supersite - Judith C. Chow; John G. Watson; Douglas H. Lowenthal; Kihong Park; Prakash Doraiswamy; Ken Bowers; Richard Bode (Environmental Monitoring and Assessment, 2008)

No evidence of endemic Borna disease virus infection in Australian horses in contrast with endemic infection in other continents - S. Kamhieh; J. Hodgson; L. Bode; H. Ludwig; C. Ward; R. L. P. Flower (Archives of Virology, 2006)

Marine Alkaloid Polycarpine and Its Synthetic Derivative Dimethylpolycarpine Induce Apoptosis in JB6 Cells Through p53- and Caspase 3-Dependent Pathways - Sergey N. Fedorov; Ann M. Bode; Valentin A. Stonik; Irina A. Gorshkova; Patricia C. Schmid; Oleg S. Radchenko; Evgueni V. Berdyshev; Zigang Dong (Pharmaceutical Research, 2004)

From DNA structure to gene expression: mediators of nuclear compartmentalization and dynamics - J. Bode; S. Goetze; H. Heng; S. A. Krawetz; C. Benham (Chromosome Research, 2003)

Effects of ENU dosage on mouse strains - Monica J. Justice; Don A. Carpenter; Jack Favor; Angelika Neuhauser-Klaus; Martin Hrabé de Angelis; Dian Soewarto; Amy Moser; Sabine Cordes; Darla Miller; Verne Chapman; John S. Weber; Eugene M. Rinchik; et al. (Mammalian Genome, 2000)

Investigation of Functional and Morphological Integrity of Freshly Isolated and Cryopreserved Human Hepatocytes - Alina Ostrowska; Donald C. Bode; Jennifer Pruss; Bahri Bilir; Gina D. Smith; Stephen Zeisloft (Cell and Tissue Banking, 2000)

Effects of very low dose and enteric-coated acetylsalicylic acid on prostacyclin and thromboxane formation and on bleeding time in healthy subjects - S. M. Bode-Böger; R. H. Böger; M. Schubert; J. C. Frölich (European Journal of Clinical Pharmacology, 1998)

Long-wavelength global gravity field models: GRIM4-S4, GRIM4-C4 - P. Schwintzer; C. Reigber; A. Bode; Z. Kang; S. Y. Zhu; F.-H. Massmann; J. C. Raimondo; R. Biancale; G. Balmino; J. M. Lemoine; B. Moynot; J. C. Marty; et al. (Journal of Geodesy, 1997)

Histones: genetic diversity and tissue-specific gene expression - D. Doenecke; W. Albig; C. Bode; B. Drabent; K. Franke; K. Gavenis; O. Witt (Histochemistry and Cell Biology, 1997)